Cas9-mediated genome editing in the methanogenic archaeon Methanosarcina acetivorans - Nayak, Dipti D. (Proc Natl Acad Sci U S A, 2017)
Although Cas9-mediated genome editing has proven to be a powerful genetic tool in eukaryotes, its application in Bacteria has been limited because of inefficient targeting or repair; and its application to Archaea has yet to be reported. Here we describe the development of a Cas9-mediated genome-editing tool that allows facile genetic manipulation of the slow-growing methanogenic archaeon Methanosarcina acetivorans. Introduction of both insertions and deletions by homology-directed repair was remarkably efficient and precise, occurring at a frequency of approximately 20% relative to the transformation efficiency, with the desired mutation being found in essentially all transformants examined. Off-target activity was not observed. We also observed that multiple single-guide RNAs could be expressed in the same transcript, reducing the size of mutagenic plasmids and simultaneously simplifying their design. Cas9-mediated genome editing reduces the time needed to construct mutants by more than half (3 vs. 8 wk) and allows simultaneous construction of double mutants with high efficiency, exponentially decreasing the time needed for complex strain constructions. Furthermore, coexpression the nonhomologous end-joining (NHEJ) machinery from the closely related archaeon, Methanocella paludicola, allowed efficient Cas9-mediated genome editing without the need for a repair template. The NHEJ-dependent mutations included deletions ranging from 75 to 2.7 kb in length, most of which appear to have occurred at regions of naturally occurring microhomology. The combination of homology-directed repair-dependent and NHEJ-dependent genome-editing tools comprises a powerful genetic system that enables facile insertion and deletion of genes, rational modification of gene expression, and testing of gene essentiality.